The Subfamily Culicinae (Diptera: Culicidae) in Kerman Province, Southern Iran - S Azari-Hamidian; MR Abai; M Mashayekhi; H Ladonni; H Vatandoost; AA Hanafi-Bojd; F Faghih-Naini; M Jedari (Tehran University of Medical Sciences, 2005)
There are some arboviral and parasitic diseases which are transmitted by culicine mosquitoes in Iran. Three genera and eleven species of the subfamily Culicinae (Diptera: Culicidae) were collected by dipping method and identified in Kahnooj district, Kerman province, south-eastern Iran, during October and November, 2003 including; Culex (Culex) bitaeniorhynchus, Cx. (Maillotia) deserticola, Cx. (Cux.) laticinctus, Cx. (Cux.) perexiguus, Cx. (Cux.) pipiens, Cx.(Cux.) quin- quefasciatus, Cx.(Cux.) sinaiticus, Cx.(Cux.) theileri, Cx.(Cux.) tritaeniorhynchus, Culiseta (Allotheobaldia) longiareolata, and Uranotaenia (Pseudoficalbia) unguiculata. In this study, Ur.unguiculata was identified in Kerman province for the first time. Fauna and ecology of Culicinae need more investigations in this province.